(untitled) (Damascus University Journal for engineering sciences, 2021)
The study of the artistic structure in the artworks of one of the greatest painters has a profound effect in raising the level of reading these artworks, the ability to analyze the visual scene, and the understanding of the system within which the elements of the artwork are consistent and organized its parts in it. And in this research Albert Moore was chosen as an artist with his own mark in the world of Art because he was able to express his artistic vision and aesthetic philosophy while keeping the academic rules in which he adhered throughout his artistic career, and this technique can be distinguished in the simplification of the form while maintaining a high level of diversity that pleasing to the eye in his artistic experiences. The artist’s goal remains to achieve the ultimate in unity with the utmost diversity, and this unity in the artwork determines its aesthetic level, and the more that the parts of the artwork are interconnected and its variations harmonize in its unity at the level of form, color, connotations, method of modification and structure of composition, the more that its composition moves away or approaches artistic and aesthetic perfection.